The effect of the Zahoric model in learning some kinetic sentences - M. Maison Mohammed Dr. Luma Sameer (الرياضة المعاصرة)
When teaching or training fencing we find that most learners are able to perform some fencing skills during learning within the lesson, but they find it difficult to perform the same skills when linked in one sentence after a short period or in subsequent lessons, or during practical exams, so I conducted those Study to develop solutions to this problem by investing the Zahoric model and its distinctive educational steps in learning the kinetic sentences in the female blinds, and its impact on the process of learning and linking kinetic sentences in the sport of fencing and make the learning process more effective and economical.